HUBUNGAN JENIS DIET VEGETARIAN DAN KONSUMSI MAKANAN SUMBER ZAT BESI DENGAN KADAR HEMOGLOBIN PADA KOMUNITAS INDONESIA VEGETARIAN SOCIETY (IVS) JAKARTA 2021 - Alfira Septi Inayah (2021)
This research was conducted to determine the relationship between the type of vegetarian diet and consumption of food sources of iron with hemoglobin level in the Indonesian Vegetarian Society (IVS) Jakarta 2021. The method of this study used an analytic observational with cross sectional design, the number of respondents was 82 people were chosen by simple random sampling from members of the Indonesian Vegetarian Society (IVS) Jakarta. Age, gender, duration of being vegetarian, reasons for being vegetarian, and type of vegetarian diet were obtained by questionnaires, consumption of iron source foods data was obtained with Semi Quantitative-Food Frequency Questionare, and hemoglobin level data obtained by EasyTouch brand of digital Hb check (GCHb). Data were analyzed by univariate and bivariate. Bivariate analysis using the Mann Whitney test. The results showed that there was a relationship between the type of vegetarian diet and hemoglobin level (p = 0.000), and there was no relationship between the consumption of iron sources and hemoglobin level (p = 0.474). It is hoped that vegetarian dieters pay attention to the consumption of iron-source foods so that hemoglobin levels are well maintained.